2016
DOI: 10.1155/2016/1284790
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of a Specialized Music Therapy Model for Children with Disabilities Delivered in a Classroom Setting

Abstract: Music therapy is gaining popularity as an intervention strategy for children with developmental disabilities, including autism spectrum disorder (ASD). This study was a pilot investigation of a classroom-based music-based intervention, Voices Together®, for improving communication skills in children with ASD and children with intellectual disabilities. Four local public elementary school special education classrooms, serving 5 children with a classification of autistic disorder and 32 children with intellectua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 24 publications
0
11
0
5
Order By: Relevance
“…Intellectual Disability (n = 361) Five non-controlled studies (40)(41)(42)(43)(44) and two controlled studies (45,46) evaluated the effect of music therapy on youths with ID (Table 3). Two studies showed a positive effect of music therapy sessions on parent-child interactions, with increased spontaneous demands by the child and adapted parental responses (41,43), more synchronous behaviors between parents and children (43), and an improvement in parents' mental health (41).…”
Section: Music Therapy For Children With Other Nddsmentioning
confidence: 99%
“…Intellectual Disability (n = 361) Five non-controlled studies (40)(41)(42)(43)(44) and two controlled studies (45,46) evaluated the effect of music therapy on youths with ID (Table 3). Two studies showed a positive effect of music therapy sessions on parent-child interactions, with increased spontaneous demands by the child and adapted parental responses (41,43), more synchronous behaviors between parents and children (43), and an improvement in parents' mental health (41).…”
Section: Music Therapy For Children With Other Nddsmentioning
confidence: 99%
“…For example, LaGasse (2014) found that, compared with children who participated in group sessions on social skills, children in group-based music therapy sessions made greater improvements in joint attention with peers, eye gaze toward others, and parental perception of social skills. Similarly, in research on an early pilot of the group-based music therapy program Voices Together (VT), which is the subject of the present investigation, Mendelson and colleagues (2016) found that children increased their communication skills across a range of developmental disabilities. At the same time, the need for group-based music therapy has grown as the field of special education looks to integrate different modalities of therapy into students’ daily routines, raising the importance of research to establish evidence-based approaches.…”
mentioning
confidence: 52%
“…First, students served as their own control group during a baseline assessment phase before intervention began; the repeated measures approach allowed the researchers to create a quasi-control and treatment group. Second, we sought to mitigate some of the variability in previous findings (e.g., Mendelson et al, 2016) by including only students in self-contained ASD classrooms. By focusing on children with ASD who have similiar deficits and concerns around communication and socialization, we hope to better understand the specific needs of one group of students rather than trying to assess all the unique needs within all special education classrooms.…”
mentioning
confidence: 99%
“…The observed neurological correspondence between children and their parents in β and low γ bands may reflect neurophysiological responsiveness of the non-speaking children to the music therapy sessions. Indeed, Thompson and McFerran (2015) contend that music therapy "creates engaging and motivating conditions for interactions with others" and Mendelson et al (2016) found that music therapy promoted verbal responsiveness in children with autism and other developmental disabilities.…”
Section: Music Therapy Contextmentioning
confidence: 99%